Pengaruh Work-life Balance terhadap Kinerja Karyawan yang di Mediasi Komitmen Organisasi - Yuan Badrianto; Muhamad Ekhsan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
The purpose of this study was to examine the effect of work-life balance on employee performance mediated by organizational commitment at PT YAUP Cikarang. This research uses quantitative methods. The research variable data collection was carried out by distributing questionnaires to as many as 50 respondents using the saturated sample method. The data analysis method used was the R-square test, Bootstrapping, Path Coefficient, and Specific indirect effects with Smart PLS software. The results of the study found that work-life balance has a positive and significant effect on employee performance, work-life balance has a positive and significant effect on organizational commitment. Organizational commitment has a positive and significant effect on employee performance. Organizational commitment can mediate the effect of work-life balance and employee performance.